Revision of a scale measuring puerpera'spositive feeling toword child-care life - TAKAHASHI, Hiroko; SHIMADA, Marie; MORI, Tomoko; ENDOH, Yuko; EMISU, Fumie; NAGAOKA, Yukiko (Journal of Japan Academy of Midwifery, 2002)
The objective of this study was the revision of Likert scale, a system for measuring thedegree of positive feelings held by new mothers as they adapt to the reordering of their livesto concentrate on taking care of their infants. The revision of the scale consisted of reducingthe number of questions to which the subjects must respond and defining the decisive characteristicsof the subjects with greater clarity. Sixteen new questions were added to the Likert scale questionnaire, which asked 28 questionsabout child-care life in 3 categories (parental role, everyday stress and positive feelingstoward infant and self), offering 9 possible response selections to each. The questionnaireswere distributed to 321 women who had given birth at one of two general hospitals in Tokyo and come in for their examinations at the stage of one month after birth. Using 309valid questionnaires that were recovered, the responses were subjectedto principal compornentanalysis. This enabled us to edit the Likert scale questionnaire into 19 questions in four categories (parental confidence, self-assurance, adaptiveness and acceptance of the father's supportiveness), offering 5 possible response selections to each. The confidence factors for each category (Cronbach's a) were between 0.63 and 0.80. The revised scale fulfills its objective of reducing the number of questions about child carewhile clearly identifying the decisive characteristics of the subjects.